1997
DOI: 10.1007/s001050050636
|View full text |Cite
|
Sign up to set email alerts
|

Rezidivierende Phlebothrombosen und Ulcera crurum als Manifestationsformen hereditärer Gerinnungsstörungen und des Klinefelter-Syndroms

Abstract: Recurrent phlebothromboses in young patients with subsequent severe postthrombotic syndrome and chronic venous leg ulcers may be caused by underlying hereditary disorders of hemostasis or may occur as part of other congenital syndromes. The most common hereditary disorders of hemostasis in this respect appear to be deficiencies of antithrombin III, protein C, and protein S, and activated protein C resistance (mutations of factor V). Less frequently, dysfibrinogenemia, increased plasminogen activator inhibitor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
2
0
2
Order By: Relevance
“…Impaired wound healing and spontaneous ulcerations in patients with Klinefelter's syndrome are said to be attributed to venous insufficiency and complicated by thromboembolic events. In some clinical reports an association of Klinefelter's syndrome with thrombophlebitis, 5 factor V Leiden mutation 6 or evidence of platelet hyperaggregability 7 had been found. Local impairment of fibrinolysis leading to the development of microthrombi may be other important factors in these thromboembolic processes 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Impaired wound healing and spontaneous ulcerations in patients with Klinefelter's syndrome are said to be attributed to venous insufficiency and complicated by thromboembolic events. In some clinical reports an association of Klinefelter's syndrome with thrombophlebitis, 5 factor V Leiden mutation 6 or evidence of platelet hyperaggregability 7 had been found. Local impairment of fibrinolysis leading to the development of microthrombi may be other important factors in these thromboembolic processes 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Leg ulcerations in patients with Klinefelter's syndrome are often attributed to venous insufficiency and complicated by thromboembolic processes. Some investigators have found an association between Klinefelter's syndrome and thrombophlebitis (3,4), or evidence of platelet hyperaggregability (5). Local impairment of fibrinolysis leading to the development of microthrombi may be another important factor in these thromboembolic processes (6).…”
Section: Discussionmentioning
confidence: 99%
“…das Antikardiolipin-Syndrom oder erhöhte Plasminogen-Aktivator-Inhibitor-(PAI-) Spiegel verantwortlich gemacht (6,10,15,17). Die Funktion von PAI besteht in der irreversiblen Bindung von Plasminogen-Aktivator, welcher so nicht mehr fibrinolysiert werden kann, mit Entwicklung von venösen und arteriellen Thromben (12,17…”
Section: Mots Clésunclassified
“…Bei Betroffenen besteht eine erhöhte Inzidenz von Varikosis, chronischer venöser Insuffizienz mit rezidivierenden Ulzera und tiefen Beinvenenthrombosen, deren Ursache bisher ungeklärt ist (3,12,13,16). Mögliche pathogenetische Faktoren werden im weiteren diskutiert.…”
unclassified